MARIA BEATRIZ DO NASCIMENTO - ENGLISH VERSION - Bastos, Morgana Abranches (Revista da Associação Brasileira de Pesquisadores/as Negros/as (ABPN), 2020)
Maria Beatriz do Nascimento was born in Aracaju in 1942 and her parents migrated with ten children to Rio de Janeiro in the 1950s. She joined the Federal University of Rio de Janeiro (UFRJ) at the age of 28 in the History course. She graduated in 1971 and started teaching in the state public school system in Rio de Janeiro, articulating her teaching practice with research. She completed her Lato Sensu in 1981, Federal Fluminense University (UFF). She scripted Ôri (1989, 131 min), a film and documentary of her own directed by sociologist and filmmaker Raquel Gerber. Her trajectory has always been related to themes such as racism and quilombos, addressing the correlation between black corporeality and space with the diasporic experiences of Africans and descendants in Brazilian lands, through the notions of “transmigration” and “transatlanticity”. She was taking her master’s degree in social communication at UFRJ, under the guidance of Muniz Sodré, when her history was brutally interrupted in 1995.